2016
DOI: 10.1074/jbc.m115.693101
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Antiviral Activity of Interleukin-35 in Response to Influenza A Virus Infection

Abstract: Interleukin-35 (IL-35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Similarly, IAV also enhances IL-35 in peripheral blood mononuclear cells, throat swabs [71], human primary lung cells, and PBMCs that induce IFN-γ expression [70]. Unlike HBV infection, NF-κb is the key component that mediates IL-35 transcription during IAV infection, and IL-35 may suppress IAV protein synthesis by inducing type I and type III IFN [71]. Furthermore, STAT1 and STAT4 signaling pathways must be activated for effective function of IL-35.…”
Section: Anti-viral Functionsmentioning
confidence: 99%
“…Similarly, IAV also enhances IL-35 in peripheral blood mononuclear cells, throat swabs [71], human primary lung cells, and PBMCs that induce IFN-γ expression [70]. Unlike HBV infection, NF-κb is the key component that mediates IL-35 transcription during IAV infection, and IL-35 may suppress IAV protein synthesis by inducing type I and type III IFN [71]. Furthermore, STAT1 and STAT4 signaling pathways must be activated for effective function of IL-35.…”
Section: Anti-viral Functionsmentioning
confidence: 99%
“…IL-35 was increasingly expression in gingival tissue and gingival crevicular fluid in chronic bacterial infection induced periodontitis (Mitani et al, 2015 ). Influenza A virus infection also induced enhancement of IL-35 in both peripheral blood mononuclear cells (PBMCs) and human primary lung cells (Chen et al, 2016 ; Wang et al, 2016 ). The elevation of IL-35 exhibited extensive antiviral activity against various viral infections (Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, our findings for IL-35 differ from a study, in which serum levels of IL-35 were significantly increased in the cirrhotic process (43) and regulated the functions of viral-specific Tregs and CD8 + T cells during chronic HBV infection, which might contribute to immunotolerance and viral persistence (33,42). However, a recent study showed that IL-35 play contradictory roles in controlling viral persistence and inhibiting inflammatory responses and have an immunosuppressive function in chronic hepatitis C virus (HCV) infection (33) and another study suggests that influenza A virus infection can induce IL-35 expression and IL-35 can activate the IFN pathway and may have a potential antiviral activity (54). These findings suggest that further studies are necessary for a better understanding of the complex regulatory mechanisms of the host antiviral response related to IL-35 during HBV infection.…”
Section: Discussionmentioning
confidence: 99%